IMPLEMENTATION OF PORTFOLIO-BASED LEARNING STRATEGIES TO IMPROVE STUDENTS 'WRITING SKILLS - Ipa Rasida; Bambang Sahono (DIADIK, 2018)
This study aims to describe the application of portfolio-based learning strategies can improve the writing skills of students. The research design used was a research action. The subject is a JUNIOR grade 8 students that add up to 22 people consists of 4 men and 18 women. The data in this study were gathered using observation sheets and test writing skills. Data analysis using statistical techniques i.e. average Test and test t. Data that cannot be analyzed with statistics is described and given arguments. The results of this study demonstrate the application of learning strategies based banwa portfolio on the Indonesian Language lessons can improve the writing skills of students. The implementation of the strategy for the pembeljan- based portifolio can be applied to other subjects